Supply of Pharmaceutical products (MENA Report, 2014)
Subject of this paper is to conclude discount agreements pursuant to [section] 130a para. 8 SGBV for drug combination levodopa / carbidopa / entacapone (ATC code N04BA03) under a so-called "open-house model." All interested and suitable pharmaceutical company will SGB V offered for drug combination levodopa / carbidopa / entacapone default under uniform conditions, as well as a single access method of the financial statements to a rebate agreement pursuant to [section] 130a para. 8. An exclusivity is not given. The order quantity is unknown at the time the agreement and in particular on the demand of the insured, the evolution of the number of insured, from the prescribing behavior of physicians contract and the delivery and storage behaviourof community pharmacies dependent. The client does not guarantee any minimum purchase quantities.